UNSUR-UNSUR ESTETIK PADA FOTO INTERIOR GEREJA KATEDRAL DI JAKARTA - Julius Andi Nugroho (Universitas Trisakti, 2010)
Abstract Media photography in interior is usually more talk about that aesthetic elemnts that summarized in frame with good composition. To produce composition and good result, lighting factors play an important role . The right lighting can produce impressions better associated with the meaning of the building itself.The need for interior pictures never recede from time to time. many purposes in the making, starting from the need of books, magazine, company profile, until the calender and postcard. And for other purposes can be more free and , illustrative, with the value of higher art, such as close up, cropping or lighting. AbstrakPeranan media fotografi dalam interior umumnya lebih berbicara tentang unsur unsur estetik yang terangkum dalam sebuah bingkai dengan komposisi yang baik. Dalam menghasilkan suatu komposisi dan hasil yang baik, faktor pencahayaan memegang peranan penting.Pencahayaan atau lighting yang tepat dapat emghasilkan kesan-kesan yang lebih baik terkait dengan makna bangunan iru sendiri